PERANAN AGAMA SEBAGAI PEREKAT KERUKUNAN DAN PEMICU KONFLIK DALAM KEMAJEMUKAN - Sutoyo Sutoyo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
In the modem era, human being was confronted by varius type of multiplicity in his daily life. In this paper, the writer focuses on religion multiplicity. Religion multiplicity cannot be avoided, and it has been Sunatullah, since the diversity ofreligion is caused by the existence of different interpretation and understanding ofthe religion lesson. Multiplicityofvarius religions majority is caused by different theology. Religious people all over the word have universal values, in the form of: wish harmonious living, happiness, respect to each other, affection and other. The Realization for is not easy since there are many baniers and constraints. To overcome the various barriers of religious life, the understanding of all religion's fol lower is needed for solution. TI1e understanding can be obtained by practicing religions tolerance and dialogue. Religious tolerance means that every religion holders has to take the different, even ifit confronts their religion lesson. Besides, the solution can also be achieved through interactive dialogue among religion holders by sitting together, talking about the real problem to find solutions, avoiding conflict, and reconciliation among themselves.